2019
DOI: 10.1016/j.chb.2019.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Elapsed time estimates in virtual reality and the physical world: The role of arousal and emotional valence

Abstract: Virtual reality (VR) allows for a close approximation of the real world, but interacting with VR differs from experiencing the real world in some key elements, one of which may be the perception of time.The main goal of the current experiment was to determine whether a time compression effect exists for VR and if so, to examine whether this is the result of the medium of VR itself, or the content used in VR.Participants viewed movie clips in either a real-life cinema or a VR replica of this cinema and were ask… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 22 publications
(21 reference statements)
1
11
1
Order By: Relevance
“…It was also shown, that fear does not affect time estimation in VR (Kitajima et al, 2020). van der Ham et al (2019) recently investigated the estimation of time duration by letting people watch video clips in VR and in the real world. They found no significant difference in the estimated time duration between VR and the real world.…”
Section: Time Studies In Virtual Realitymentioning
confidence: 99%
“…It was also shown, that fear does not affect time estimation in VR (Kitajima et al, 2020). van der Ham et al (2019) recently investigated the estimation of time duration by letting people watch video clips in VR and in the real world. They found no significant difference in the estimated time duration between VR and the real world.…”
Section: Time Studies In Virtual Realitymentioning
confidence: 99%
“…VR has also been used to induce temporal recalibration by coupling the movement of individuals to the speed of events in the virtual environment (the slower participants moved, the slower the events unfolded and vice versa), which led to underreproduction of time intervals in a subsequent psychophysical task (Bansal et al, 2019). More in line with the objectives of this study, van der Ham et al (2019) found no difference in the duration estimations of clips watched in a VR and in a real-life cinema, challenging the preconception that VR accelerates the passage of time.…”
mentioning
confidence: 77%
“…a more immersive experience), although Matthews, Stewart & Weardon (2011) argue that this may not be entirely accurate. Altered time perception may not necessarily be due to the VE, but rather the particular level and type of stimuli of a given VE or task(s) within a VE (van der Ham, Klaassen, van Schie & Cuperus, 2019). This suggests that perceived time accuracy in VEs depend upon a myriad of factors, including simulation or technology medium, length of exposure, visual and auditory conditions, passive vs. active engagement, emotional context and individual factors of the users themselves.…”
Section: Discussionmentioning
confidence: 99%
“…years, days, hours, seconds, etc.) (Seow, 2008). Different technologies and systems are used to define, organize, measure and ultimately objectify "time" (Seow, 2008).…”
Section: Introductionmentioning
confidence: 99%